Derma-Hair - Aplicativo Móvel Para Auxílio Diagnóstico Das Dermatoses Capilares - Acacio, Glayce Josy Sasaki [UNIFESP] (2018)
Introduction: Trichoscopy is raising a growing interest among dermatologists. Nonetheless, the clinical diagnosis of scalp diseases is not always clear and objective. Objective: To develop a mobile application for capillary dermatoses diagnosis. Method: Design Thinking methodology is divided into four phases: Phase 1 - Discover: Desk research was conducted by searching the databases SciELO/Pubmed/LILACS and by searching Google and Scholar Google websites. Once the target audience was selected, interviews were conducted; Phase 2 – Define: the difficulties of the interviewees were mapped; Phase 3 - Develop: a brainstorming was conducted with three interviewees; Phase 4 – Deliver: prototyping, validation and elaboration of the final version of the application. Results: Phase 1 – Discover: We identified 2 applications related to dermatoscopy of the scalp and the interviews were performed; Phase 2 – Define: the main problem of the interviewees is lack of experience and theoretical-practical knowledge regarding the handling of the dermatoscope and the diagnosis of hair and scalp pathologies. Phase 3 -Developing: the solution proposed through brainstorming consisted of an application that would allow access to support materials for the best diagnosis of capillary dermatoses through tricoscopy; the information and database of the application were defined; Phase 4 - Deliver: a prototype with content skeleton and interactive video presented for validation. After approval, the interactive website was developed, and turned available to the public. Conclusion: Derma-hair was developed to improve the knowledge and diagnosis of hair and scalp pathologies.